Peran Guru Fiqh dalam Meningkatkan Akhlak Santri Kelas VII di Madrasah Diniyah Takmiliyah Dayah Bustanul Arifin Putri - Pata, Akmal; Rahmah, Syarifah; muhajir, Al (Pascasarjana IAIN Lhokseumawe, 2022)
ABSTRACTThe teacher's role in the learning process has a very large influence and is a benchmark for success and moral improvement, but what has happened in this Madrasah is different, for several reasons. First, every disciplined student enters when the school or madrasa bell rings with the start of reading nadhom shorfiyah for grade level Wusho and nadhom alfiyah for Ulya level. Second, every student when the teacher passes, they are silent for a moment to wait for the teacher to pass. Third, every student who does not understand the lesson. will ask if the teacher has not finished explaining or is allowed to ask. Fourth. One of the behaviors of the students of Madrasah Diniyah Takmiliyah Dayah Bustanul Arifin Putri is to wash the clothes and iron the clothes of the teachers without being asked and to turn the sandals of each teacher with the aim of obtaining blessings from the teacher. The results of the study show the role of the Fiqh teacher in improving the morals of students. Methods in the teaching and learning process are the methods used in teaching and learning activities or conveying material, which consists of the question and answer method, the lecture method, the memorization method, and the demonstration method. each, learning materials that are systematically arranged, the availability of facilities for the needs of students and both external factors of financial support to carry out various programs and activities originating from various stakeholders.Keywords: The role of the teacher, Jurisprudence, Moral Improvement